2017
DOI: 10.5811/westjem.2017.5.34152
|View full text |Cite
|
Sign up to set email alerts
|

Increased Computed Tomography Utilization in the Emergency Department and Its Association with Hospital Admission

Abstract: IntroductionOur goal was to investigate trends in computed tomography (CT) utilization in emergency departments (EDs) and its association with hospitalization.MethodsWe conducted an analysis of an administrative claims database of U.S. privately insured and Medicare Advantage enrollees. We identified ED visits from 2005 through 2013 and assessed for CT use, associated factors, and hospitalization after CT, along with patient demographics. We used both descriptive methods and regression models adjusted for year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
67
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(78 citation statements)
references
References 55 publications
1
67
0
1
Order By: Relevance
“…Though several observational studies have assessed the value of such tools at potentially reducing unnecessary CTH [ 2 ], it is not clear that such efforts have led to reduction in CTH usage. Rather, data suggest that CTH use in emergency departments is increasing [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Though several observational studies have assessed the value of such tools at potentially reducing unnecessary CTH [ 2 ], it is not clear that such efforts have led to reduction in CTH usage. Rather, data suggest that CTH use in emergency departments is increasing [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that ED imaging volume decreased substantially during the COVID-19 pandemic [3,4,6]. This contrasts with the pre-pandemic trend in ED imaging, particularly CT, which had been increasing for the past decade [14][15][16], as convincing data has shown that early CT diagnosis of certain conditions, such as appendicitis and uncomplicated diverticulitis, reduces hospital resource use and improves patient outcomes [17,18]. There are several potential reasons why ED CT volume decreased during the COVID-19 pandemic, as one would expect the incidence of diseases requiring an abdominopelvic CT in the ED should remain constant or increased.…”
Section: Discussionmentioning
confidence: 97%
“…Other potential reasons may be an improvement of existing imaging technology, fear of litigation, or change of institutional culture, for example attitudes towards risk of missing diagnoses. Because of the increasing number of patients and the increase in the use of imaging [ 26 , 27 ], efficient use of CT scanning is now more required than ever [ 8 ].…”
Section: Discussionmentioning
confidence: 99%